Recurrent, refractory, metastatic and/or unresectable pediatric sarcomas: treatment options for young people ''off the roadmap''. Issue 5 (October 2008) - Anderson, Pete; Kornguth, David; Ahrar, Kamran; Hughes, Dennis; Phan, Phil; Huh, Winston; Cornelius, Kathleen; Mahajan, Anita
Although sarcoma surgery is very important for cancer control, it is not always possible or practical to offer in some situations, including sarcoma recurrences, metastatic disease and/or unacceptable loss of function. We review some pragmatic approaches and examples of how to balance indications, risks and alternatives to control cancer in young people with sarcomas that are no longer using ''front-line'' therapy. Radiotherapy combined with chemotherapy and outpatient ''continuation'' chemotherapy regimens using drugs that cause less alopecia can improve function and quality of life. Some effective strategies to help cope when cure is not possible may include tumor ablation techniques performed in interventional radiology and percutaneous nerve blocks. Family centered care and effective problem solving of difficult issues can be greatly facilitated by consultation with a multidisciplinary team experienced in the management of very difficult cases. Treatment of young people with recurrent, relapsed and/or metastatic sarcoma still remains an art very much in the realm of compassion not protocol and persistent advocacy is required for the young person for whom cure may not be possible. A reduction of suffering and assistance in writing more chapters of a rich life narrative is the goal.